Development of a non-radiometric method for estimation of Iodothyronine 5’- deiodinase type ii Activity in rat brain - SAMITA KUNDU; ARUN K RAY (International Journal of Pharma and Bio Sciences, 2017)
Iodothyronine 5’-deiodinase type II (DII) is an important enzyme catalyzing the conversion of about 75% of T4 to T3 in brain. Determination of this enzyme activity reported so far, involved use of hazardous radioactive methods. We have ventured to modify the earlier radioactive method by an exclusively non-radiometric procedure. The cerebral cortex of rats were carefully dissected out, homogenized and centrifuged to obtain a post-mitochondrial preparation for assessing DII activity.The preparation was incubated in a suitable non-radioactive assay medium for T4 to T3 conversion. The T3 formed, was detected and estimated by competitive enzyme immunoassay and DII activity was expressed indirectly in terms of fmoles T3 formed/min/mg protein. The validity of this method has been checked by using a DII inhibitor, iopanoic acid, and also by an anti-thyroid drug PTU (propyl thiouracil) that does not inhibit DII. This method can, thus, be a novel and quick indirect method of assaying DII activity of cerebral cortex non-radiometrically.